Coupling of semiconductor carbon nanotubes emission with silicon photonic micro ring resonators - Sarti, Francesco; Caselli, Niccolo; La China, Federico; Biccari, Francesco; Torrini, Ughetta; Intonti, Francesca; Vinattieri, Anna; Duran-Valdeiglesias, Elena; Zhang, Weiwei; Noury, Adrien; Alonso-Ramos, Carlos; Hoang, Thihong Cam; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2016)
Hybrid structures are needed to fully exploit the great advantages of Si photonics and several approaches have been addressed where Si devices are bonded to different materials and nanostructures. Here we study the use of semiconductor carbon nanotubes for emission in the 1300 nm wavelength range to functionalize Si photonic structures in view of optoelectronic applications. The Si micro-rings are fully characterized by near field forward resonant scattering with 100 nm resolution. We show that both TE and TM modes can be addressed on the top of the micro-rings in a vectorial imaging of the in-plane polarization components. We coupled the Si micro-resonators with selected carbon nanotubes for high photoluminescence emission. Coupling nanotubes with the evanescent tails in air of the electric field localized in the photonic modes of the micro-resonators is demonstrated by sharp resonances over imposed to the nanotube emission bands. By mapping the Si and the nanotube emission we demonstrate that strong enhancement of the nanotube photoluminescence can be achieved both in the photonic modes of micro-disks and slot micro-rings, whenever the spatial overlap between nano-emitters and photonic modes is fulfilled.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon nanotubes; Near field optics; Photoluminescence mapping; Si photonics